2011
DOI: 10.1182/blood-2010-11-321521
|View full text |Cite
|
Sign up to set email alerts
|

The SKP2 E3 ligase regulates basal homeostasis and stress-induced regeneration of HSCs

Abstract: Exit from quiescence and reentry into cell cycle is essential for HSC self-renewal and regeneration. Skp2 is the F-box unit of the SCF E3-ligase that targets the CDK inhibitors (CKIs) p21 Cip1 , p27 Kip1 , p57 Kip2 , and p130 for degradation. These CKIs inhibit the G 1 to S-phase transition of the cell cycle, and their deletion results in increased cell proliferation and decreased stem cell self-renewal. Skp2 deletion leads to CKIs stabilization inducing cell-cycle delay or arrest, and conversely, increased S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 40 publications
(57 reference statements)
3
31
0
Order By: Relevance
“…Two recent articles (96,97) confirmed the central role played by decreased p57 Kip2 in the exit from quiescence and reentry into the cell cycle, which are essential for HSC self-renewal and regeneration. The first investigation showed that SKP2 expression (and thus p57 Kip2 degradation) is increased in HSC and progenitors in response to hematopoietic stress from myelosuppression or after transplantation (96). The study also suggested a previously unrecognized role for SKP2 in regulating HSC and progenitor expansion and hematopoietic regeneration after stress.…”
Section: P57 Kip2 Metabolismmentioning
confidence: 91%
See 1 more Smart Citation
“…Two recent articles (96,97) confirmed the central role played by decreased p57 Kip2 in the exit from quiescence and reentry into the cell cycle, which are essential for HSC self-renewal and regeneration. The first investigation showed that SKP2 expression (and thus p57 Kip2 degradation) is increased in HSC and progenitors in response to hematopoietic stress from myelosuppression or after transplantation (96). The study also suggested a previously unrecognized role for SKP2 in regulating HSC and progenitor expansion and hematopoietic regeneration after stress.…”
Section: P57 Kip2 Metabolismmentioning
confidence: 91%
“…A subsequent investigation suggested that p57 Kip2 is responsible for the G 0 /G 1 block of HSC and that its decrease is required for S entry (95). Two recent articles (96,97) confirmed the central role played by decreased p57 Kip2 in the exit from quiescence and reentry into the cell cycle, which are essential for HSC self-renewal and regeneration. The first investigation showed that SKP2 expression (and thus p57 Kip2 degradation) is increased in HSC and progenitors in response to hematopoietic stress from myelosuppression or after transplantation (96).…”
Section: P57 Kip2 Metabolismmentioning
confidence: 97%
“…These defects in ROS high HSCs were associated with an increased activation of p38 MAPK (p38) and mammalian target of rapamycin (mTOR), which could be attenuated by the treatment with an antioxidant, a p38 inhibitor, or rapamycin. Furthermore, incubation of mouse BM HSCs with high concentrations of BSO resulted in a dramatic reduction in HSC clonogenicity (Juntilla et al, 2010; Rodriguez et al, 2011). In addition, increased production of ROS has been found to have a cause and effect relationship with HSC defects in various pathological conditions.…”
Section: Ros and Normal Stem Cellsmentioning
confidence: 99%
“…These data suggest that Dup may be the target substrate for the SCF complex being studied, with a secondary target possibly being Cyclin E. Previous research in human cells has shown that SCF Skp2 regulates the degradation of Cdt1 (the homolog of Drosophila Dup) [32]. It has also been shown that the activated SCF Skp2 complex plays a role in murine hematopoiesis, by ubiquitinating proteins necessary for proper cell cycle, such as Cyclin E. There are still many questions to be answered about SCF regulation in blood cells, as some of these results are contradictory [36-38]. …”
Section: Discussionmentioning
confidence: 99%